Investigating the transportation of nonpolar solvent mixtures through organic solvent nanofiltration (OSN) membranes - Pan, Yanxin (Nanyang Technological University, 2024)
Organic Solvent Nanofiltration (OSN) is a pressure-driven membrane process that is used in solvent separation and recovery. This project aims to study the solvent transportation and separation performance of commercial OSN membranes (GMT-oNF-2 membranes, purchased from BORSIG Membrane Technologies) for nonpolar solvent mixtures. Different characterization tests for OSN membranes, each with a different purpose, were utilized to investigate the membrane physiochemical properties.